Screening for thyroid disorders in asymptomatic adults from Brazilian populations - Benseñor, Isabela (São Paulo Medical Journal, 2002)
Advances in thyroid disorder diagnosis have created new thyroid disorder categories such as subclinical hyperthyroidism and subclinical hypothyroidism. In the 1980s, immunometric assaying for thyroid stimulating hormone (TSH) emerged and became defined as the most cost-effective test in thyroid disorder screening. The second step in the screening of thyroid disorders is to determine free thyroxine (FT4), and cost-effective methods for its detection are now available. Using TSH and FT4, it is possible to determine four situations: clinical hyperthyroidism, clinical hypothyroidism, subclinical hyperthyroidism and subclinical hypothyroidism. Subclinical hypothyroidism can be a strong indicator of risk for atherosclerosis and myocardial infarction in elderly women. Cardiovascular mortality among Brazilian women is one of the highest in the Western world. The best-known risk factors for cardiovascular diseases are high blood pressure, smoking, diabetes, and hypercholesterolemia. Although these are recognized as primary risk factors, there are other risk factors that could be identified as primordial risk factors. This may be the case for subclinical hypothyroidism. Early detection of thyroid disorders in women over fifty could be a highly cost-effective option in the prevention of cardiovascular disorders among Brazilian women.